Molecular mapping of the AOX1a and β-AmyI genes in potato - Krusiewicz, Dominika; Jakuczun, Henryka; Wasilewicz-Flis, Iwona; Strzelczyk-Żyta, Danuta; Marczewski, Waldemar (Plant breeding, 2011)
With 1 figure and 1 table ABSTRACT: Two genes, AOX1a and β-AmyI, were mapped in diploid potato. AOX1a (alternative oxidase 1a) is the cyanide insensitive component of the electron transport chain in plants induced by environmental stress. The enzyme β-amylase (β-AmyI) is involved in hydrolytic starch breakdown in both photosynthetic and storage organs. AOX1a and β-AmyI are located in the central region on potato chromosome VIII, where other genes for potato tuber quality traits were mapped.